Efektivitas Bimbingan Klasikal Melalui Video Podcast dalam Meningkatkan Motivasi Berprestasi Mahasiswa - Feridho, Richard; Rasmanah, Manah; Janare Putra, Bela (Social Science and Contemporary Issues Journal, 2024)
This research is entitled "The Effectiveness of Classical Guidance Through Video Podcasts in Increasing Student Achievement Motivation." Motivation for achievement that occurs in students of the Islamic Counseling Guidance study program class of 2023 actually still has relatively low self-motivation in achieving, which can be seen from each observation. conducted by researchers on each client. The aim of this research is to find out how before and after being given video podcasts, classical guidance is proven to be effective in increasing student motivation. This research method uses a quantitative approach with an experimental research type and a one group pretest - posttest design. From a total population of 80 students, 14 samples were taken. The sample technique used was purposive sampling. Data collection techniques include observation, questionnaires and documentation. With a total of 30 questions, the validity test of rcount > rtable has been carried out with rcount values ​​of 0.256 – 0.566 and rtable 0.2. The data analysis technique uses the T test. The results of the research show that the level of student achievement motivation was initially M(SD) = 76.1 (2.9) to M(SD) = 88.1(1.4). With a T test result of 14.538. Greater than the t table (5%) with a t table result of 1.7709. Therefore, classical guidance through video podcasts is effective in increasing student achievement motivation.